Current and Future Exposure of Infrastructure in the United States to Natural Hazards - Willis, Henry H. (RAND Corporation, 2016)
Communities, companies, and governments at all levels in the United States are making decisions that will influence where, what and how infrastructure will be built. This report describes insights about exposures from natural hazards now and in the future, as well as gaps in data that, if filled, could improve the nation's ability to assess infrastructure risk and improve infrastructure resilience.